Evaluasi Fungsional dan Kenyamanan Ruang Toilet dan Tempat Wudhu Masjid Kampus di Kota Pontianak - Muhammad Nurhamsyah; Alhamdani, M. Ridha; Syaiful Miazir; Lestari; O’i Prasesti (Nature: National Academic Journal of Architecture, 2024)
The Campus Mosque is a worship facility for Muslims, which accommodates all kinds of worship activities in the campus environment. In general, the mosque is used as a place to worship, for religious activities such as grand tabling, recitation, and lectures, and a place to stop for travelers and others. The existence of the Campus Mosque is inseparable from its supporting facilities for the convenience and continuity of the congregation in worship, one of which is the toilet room facility and the ablution area. These two facilities are always kept clean and comfortable, making it easier for the congregation to wash and clean themselves before worship. This study aims to evaluate the functional and behavioral aspects of using toilet room facilities and ablution places. It can provide recommendations for evaluation results and design solutions for toilet rooms and ablution places that are healthy and comfortable according to Islamic law. This research was conducted on three objects: toilet room facilities and ablution places at the Al Muhtadin UNTAN Campus Mosque, Al Hadid POLNEP Mosque, and Al Baroqah IKIP Pontianak Mosque. The research method used is Post Occupancy Evaluation (POE) with an investigative level, carried out by observing field data collection, observing behavior by means of a place center map, and distributing questionnaires by random sampling. Then, the data is processed using qualitative analysis by describing the results of the questionnaire that was obtained. The results of the study show that from the functional evaluation, there are non-standard dimensions of the toilet room, access to circulation from the toilet, and integrated ablution place. Comfort from the behavioral aspect based on observation, there is a tendency for users to choose access that is closer to the toilet room and the place of ablution. Based on respondents, the level of comfort, convenience, and security also focuses on supporting physical elements, zones between toilet rooms and ablutions that are comfortable and safe to access, and flexible movement between users. The conclusion matrix of the evaluation results is used as the basis for providing solutions and recommendations for the spatial layout of toilets and ablution places that are representative by taking into account aspects of shariah and function feasibility.